2013
DOI: 10.3390/ijerph110100487
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Impact of Firearms Restrictions on Fatal Firearm Injuries in Males: A National Observational Study

Abstract: Introduction: Public health organizations have recommended restricted access and safe storage practices as means to reduce firearm injuries and deaths. We aimed to assess the effect of four firearm restrictions on firearm deaths in Norway 1969–2009. Methods: All deaths due to firearm discharge were included (5,660 deaths, both sexes). The statistical analysis to assess impact of firearm legislations was restricted to males because of the sex disproportionality (94% were males). Results: A total of 89% of firea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
2
23
0
1
Order By: Relevance
“…Greater symptom severity and/or availability of psychiatric medication could explain our finding of even higher risks for suicide and accidental poisoning in those with major mental health impairment 39. On the other hand, in Norway, manifest psychiatric disorders at such young age would normally lead to treatment, follow-up or reduced access to lethal means (such as firearms or medications), with the potential to prevent suicide and unintentional injury/accident death 40. Future cohort studies including more detailed clinical information will be useful to elucidate the relative contributions of treatment and psychological/behavioural risk factors on cause-specific types of suicide and unintentional injury/accident death.…”
Section: Discussionmentioning
confidence: 91%
“…Greater symptom severity and/or availability of psychiatric medication could explain our finding of even higher risks for suicide and accidental poisoning in those with major mental health impairment 39. On the other hand, in Norway, manifest psychiatric disorders at such young age would normally lead to treatment, follow-up or reduced access to lethal means (such as firearms or medications), with the potential to prevent suicide and unintentional injury/accident death 40. Future cohort studies including more detailed clinical information will be useful to elucidate the relative contributions of treatment and psychological/behavioural risk factors on cause-specific types of suicide and unintentional injury/accident death.…”
Section: Discussionmentioning
confidence: 91%
“…This question, though, of what impact laws and policies have on firearm-related violence is incredibly difficult to answer [17]. Although there are many individual studies that tie firearms to violence, a systematic review of all available literature could not conclusively state that regulatory efforts put in place to curtail gun violence actually impacted such violence at all [8].…”
Section: Protecting Society Vs Individual Rightsmentioning
confidence: 95%
“…Seventy-five percent of the boys played with the real firearm, despite 75 % of the parents feeling sure that their child would not touch the real firearm and would play with the water gun only [1]. Another study looked at over 60,000 suicides among youth aged [14][15][16][17][18][19][20] and found that the CAP laws did not decrease the overall rates of suicide among the youth [7]. Yet, it does appear that CAP has a great effect on morbidity and mortality in states that have more strict penalties related to firearm possession and violence [10].…”
Section: Children and Firearmsmentioning
confidence: 99%
“…41 Male firearm usage is heavily influenced by substance use and impulsivity. 53 Male gender, binge drinking, drug use, violence involvement, and ED utilization are all independently associated with firearm access. However, firearm use is not entirely a “male” problem: although knives are the most frequently reported weapon of choice among female youth, 35 female firearm use is on the rise.…”
Section: Gender Substance Use and Firearm Violencementioning
confidence: 99%
“…10 They are also the leading cause of death by suicide. 28,53 Substance use increases the risk of firearm-related injuries and death for both sexes. 41 …”
Section: Gender Substance Use and Firearm Violencementioning
confidence: 99%